INTERNET DALAM BINGKAI DAKWAH ORGANISASI NAHDLATUL ULAMA - muhammad itsbatul haq (JURNAL INDO-ISLAMIKA, 2018)
This article focuses on the activities of the preaching of Nahdlatul Ulama as one of the religious organizations in Indonesia in the realm of the internet world. Nahdlatul Ulama (NU) is considered an Islamic organization that is anti-technological development. This assumption was born as a result of the wrong view of evaluating Nahdlatul Ulama as a pioneer of the traditionalist group due to the mismatch between religion and modernity. For Nahdlatul Ulama itself, the internet can be used as a useful medium for religion and can be used as a medium for deradicalization. The positive response of religion is seen in the use of the internet by Nahdlatul Ulama which is categorized into four forms of use, namely ideological, contextual, polemical and strategic use. All of these forms indicate that the internet as part of modernity can be used for the benefit and broadcast of religious information.